Using miniaturized radiotelemetry to discover the breeding grounds of the endangered New Zealand Storm Petrel Fregetta maoriana. (7th August 2015) - Rayner, Matt J.; Gaskin, Chris P.; Fitzgerald, Neil B.; Baird, Karen A.; Berg, Martin M.; Boyle, David; Joyce, Leigh; Landers, Todd J.; Loh, Graeme G.; Maturin, Sue; Perrimen, Lyndon; Scofield, R. Paul; et al.
<x xml:space="preserve">Abstract</x> Identification of breeding sites remains a critical step in species conservation, particularly in procellariiform seabirds whose threat status is of global concern. We designed and conducted an integrative radiotelemetry approach to uncover the breeding grounds of the critically endangered New Zealand Storm Petrel Fregetta maoriana (NZSP), a species considered extinct before its rediscovery in 2003. Solar‐powered automated radio receivers and hand‐held telemetry were used to detect the presence of birds on three island groups in the Hauraki Gulf near Auckland, New Zealand. At least 11 NZSP captured and radiotagged at sea were detected at night near Te Hauturu‐o‐Toi/Little Barrier Island with the detection of an incubating bird leading to the discovery of the first known breeding site for this species. In total, four NZSP breeding burrows were detected under mature forest canopy and three adult NZSP and two NZSP chicks were ringed. Telemetry data indicated NZSP showed strong moonlight avoidance behaviour over the breeding site, had incubation shifts of approximately 5 days and had a breeding season extending from February to June/July, a different season from other Procellariiformes in the region. Radiotelemetry, in combination with rigorously collected field data on species distribution, offers a valuable technique for locating breeding grounds of procellariiform seabirds and gaining insights into breeding biology while minimizing disturbance to sensitive species or damage to fragile habitat. Our study suggests an avenue for other breeding ground searches in one of the most threatened avian Orders, and highlights the general need for information on the location of breeding sites and understanding the breeding biology in data‐deficient birds.